A population-based epidemiologic study of adult neuromuscular disease in the Republic of Ireland. (17th January 2017) - Lefter, Stela; Hardiman, Orla; Ryan, Aisling M.
Abstract : Objective: To estimate the prevalence rates (PRs) of acquired and inherited neuromuscular diseases (NMD) in the adult Irish population, reflecting the burden of these conditions in a single country. Methods: This population-based study was performed in the Republic of Ireland (RoI), with a PR estimated for December 2013. Multiple case ascertainment sources were utilized. Demographic and clinical information and relevant diagnostic results were registered. Results: A total of 2, 641 adults were identified, giving a PR of 62.6/100, 000 (95% confidence interval [CI] 59.95–65.24) for all NMD in RoI. Disease-specific PR include chronic inflammatory demyelinating polyradiculoneuropathy 5.87/100, 000 (95% CI 5.06–6.68), Charcot-Marie-Tooth 10.52/100, 000 (95% CI 9.44–11.61), hereditary neuropathy with liability to pressure palsies 0.84/100, 000 (95% CI 0.54–1.15), myotonic dystrophy type I 6.75/100, 000 (95% CI 5.88–7.61), Duchenne muscular dystrophy 3.0/100, 000 (95% CI 2.33–3.70), Becker muscular dystrophy 2.2/100, 000 (95% CI 1.64–2.88), facioscapulohumeral dystrophy 2.59/100, 000 (95% CI 2.05–3.13), limb-girdle muscular dystrophy 2.88/100, 000 (95% CI 2.31–3.45), periodic paralysis 1.72/100, 000 (95% CI 1.28–2.15), myotonia congenita 0.32/100, 000 (95% CI 0.18–0.56), paramyotonia congenita 0.15/100, 000 (95% CI 0.06–0.34), Kennedy disease 0.83/100, 000 (95% CI 0.40–1.27), Lambert-Eaton myasthenic syndrome 0.29/100, 000 (95% CI 0.11–0.47), myasthenia gravis 15.12/100, 000 (95% CI 13.82–16.42), and sporadic inclusion body myositis 11.7/100, 000 (95% CI 9.82–13.58). PR for amyotrophic lateral sclerosis was established from an existing Register as 7.20/100, 000 (95% CI 6.34–8.15). Conclusions: The PR of all adult NMD in RoI is relatively high when compared with other chronic neurologic disorders, although some figures may be an underestimate of the true prevalence. The data provide a framework for international comparison and service planning.